Economic evaluation of betibeglogene autotemcel (Beti-cel) gene addition therapy in transfusion-dependent β-thalassemia - Anuraag R. Kansal (Taylor & Francis Group, 2021)
Background Standard of care (SoC) for transfusion-dependent β-thalassemia (TDT) requires lifelong, regular blood transfusions as well as chelation to reduce iron accumulation. Objective This study investigates the cost-effectiveness of betibeglogene autotemcel (‘beti-cel’; LentiGlobin for β-thalassemia) one-time, gene addition therapy compared to lifelong SoC for TDT. Study design Microsimulation model simulated the lifetime course of TDT based on a causal sequence in which transfusion requirements determine tissue iron levels, which in turn determine risk of iron overload complications that increase mortality. Clinical trial data informed beti-cel clinical parameters; effects of SoC on iron levels came from real-world studies; iron overload complication rates and mortality were based on published literature. Setting USA; commercial payer perspective Participants TDT patients age 2–50 Interventions Beti-cel is compared to SoC. Main outcome measure Incremental cost-effectiveness ratio (ICER) utilizing quality-adjusted life-years (QALYs) Results The model predicts beti-cel adds 3.8 discounted life years (LYs) or 6.9 QALYs versus SoC. Discounted lifetime costs were $2.28 M for beti-cel ($572,107 if excluding beti-cel cost) and $2.04 M for SoC, with a resulting ICER of $34,833 per QALY gained. Conclusion Beti-cel is cost-effective for TDT patients compared to SoC. This is due to longer survival and cost offset of lifelong SoC.